Inhibition of Quorum Sensing Regulated Virulence Factors and Biofilm Formation by Eucalyptus globulus against Multidrug-Resistant Pseudomonas aeruginosa - Pankaj Kumar Sagar; Poonam Sharma; Rambir Singh (Korean Pharmacopuncture Institute, 2022)
Objectives: The quorum-sensing-inhibitory and anti-biofilm activities of the methanol extract of E. globulus leaves were determined against clinically isolated multidrug-resistant Pseudomonas aeruginosa. Methods: The preliminary anti-quorum-sensing (AQS) activity of eucalyptus was investigated against a biosensor strain Chromobacterium violaceum ATCC 12472 (CV12472) by using the agar well diffusion method. The effect of sub-minimum inhibitory concentrations (sub-MICs) of the methanol extract of eucalyptus on different quorum-sensing-regulated virulence factors, such as swarming motility, pyocyanin pigment, exopolysaccharide (EPS), and biofilm formation, against clinical isolates (CIs 2, 3, and 4) and reference PA01 of Pseudomonas aeruginosa were determined using the swarm diameter (mm)-measurement method, chloroform extraction method, phenol (5%)-sulphuric acid (concentrated) method, and the microtiter plate assay respectively, and the inhibition (%) in formation were calculated. Results: The preliminary AQS activity (violacein pigment inhibition) of eucalyptus was confirmed against Chromobacterium violaceum ATCC 12472 (CV12472). The eucalyptus extract also showed concentration-dependent inhibition (%) of swarming motility, pyocyanin pigment, EPS, and biofilm formation in different CIs and PA01 of P. aeruginosa. Conclusion: Our results revealed the effectiveness of the E. globulus extract for the regulation of quorum-sensing-dependent virulence factors and biofilm formation at a reduced dose (sub-MICs) and suggest that E. globulus may be a therapeutic agent for curing and controlling bacterial infection and thereby reducing the possibility of resistance development in pathogenic strains.